2017
DOI: 10.3945/ajcn.116.141390
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions and the ω-6-to-ω-3 fatty acid ratio: a cross-sectional study

Abstract: Background: The v-6 (n-6) to v-3 (n-3) fatty acid (FA) ratio (n-6:n-3 ratio) was previously shown to be a predictor of executive function performance in children aged 7-9 y. Objective: We aimed to replicate and extend previous findings by exploring the role of the n-6:n-3 ratio in executive function performance. We hypothesized that there would be an interaction between n-3 and the n-6:n-3 ratio, with children with low n-3 performing best with a low ratio, and those with high n-3 performing best with a high ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 68 publications
0
10
1
1
Order By: Relevance
“…In a related issue, the balance between the n-6 and n-3 pathways determines the metabolic progression as the pathways compete for enzymes. We have shown that cognitive abilities are compromised in the individual when the n-6:n-3 balance is off [55,56]. Importantly, placental metabolism of fatty acids is differentially affected by imbalances between the n-6 and n-3 pathways [57,58].…”
Section: Docosahexaenoic Acidmentioning
confidence: 94%
“…In a related issue, the balance between the n-6 and n-3 pathways determines the metabolic progression as the pathways compete for enzymes. We have shown that cognitive abilities are compromised in the individual when the n-6:n-3 balance is off [55,56]. Importantly, placental metabolism of fatty acids is differentially affected by imbalances between the n-6 and n-3 pathways [57,58].…”
Section: Docosahexaenoic Acidmentioning
confidence: 94%
“…But some studies have pointed out that ω-3 and ω-6 fatty acids intake may play a role in the pathogenesis of cognitive decline due to the prevailing mechanisms such as oxidative stress, inflammation, and vascular risk factors [21,22]. However, several studies have suggested that ω-3 and ω-6 fatty acids and their ratio could be associated with cognitive performance among elderly people [23][24][25]. Specifically, a low ratio of ω-6 to ω-3 fatty acids in the diet might reduce the risk of cognitive decline [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to understand fatty acid consumption as part of the overall diet to align recommendations and scientific research with actual practice. Much has been made of the imbalanced consumption of fatty acids over recent decades [ 1 4 ] due to the demonstrated importance of fatty acids to the brain [ 5 – 8 ] and cognitive function [ 9 12 ]. Data from food commodities have indicated increasing imbalance in the n-6/n-3 ratio in the food supply over time [ 2 , 13 ], with some reviews indicating ratios above 20:1 [ 1 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, there isn’t any evidence that there should be such a large difference in the balance consumed by males and females 9 to 13 years old. If anything, recent evidence points to lower ratios during puberty (for both sexes) to support brain changes occurring during that time [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation